KANDUNGAN NDF (Neutral Detergen Fiber), ADF (Acid Detergen Fiber) DAN TANIN KULIT PISANG GOROHO FERMENTASI - Sri Suryaningsih Djunu (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2022)
This study aims to test and evaluate the content of NDF, ADF and tannins in fermented Goroho banana peels. The study used a completely randomized design (CRD) method with 6 treatments and 5 replications. The feed treatment consisted of T0: Goroho banana peels without fermentation, T1: Goroho banana peels fermented by Rhizopus oligosphorus 0.3% incubated for 48 hours,T2: Goroho banana peels fermented by Trichoderma viride 0.3% incubated for 120 hours. T3: Goroho banana peelsfermentedby Rhizopus oligosphorus 0.15% incubated for 48 hours, then continued with fermentation with Trichoderma viride 0.15% incubated for 120 hours. T4: Goroho banana peels fermented by Trichoderma viride 0.15% incubated for 120 hours, then continued with fermentation with Rhizopus oligosphorus 0.15% incubated for 48 hours. T5: Goroho banana peels fermented by Rhizopus oligosphorus 0.15% + Trichoderma viride 0.15% incubated for 120 hours. Variables consist of NDF, ADF and tannins content. The results showed that the fermentation of Goroho banana peels using Rhizophus oligosprus and Trichoderma viride (T1-T5) was not able to reduce the NDF and ADF fiber components, but it could reduce the tannins content by 64.24% from 0.56, decreased by 0.20% in T1 and 32.14% from 0.56 decreased to 0.51% at T4